Slime, molds, and fungi - Pascoe, Elaine; Kuhn, Dwight (Woodbridge, Conn. : Blackbirch Press, 1999)
Using hands-on natural science projects, explores and explains different types and characteristics of fungi.
Includes bibliographical references (p. 47) and index.
Wilson's Children.
Wilson's Junior High School.
School Library Journal.
6.6
3-6
Keywords: Fungi -- Juvenile literature; Fungi -- Experiments -- Juvenile literature; Fungi; Fungi -- Experiments; Experiments; Fungi; Biology -- Experiments; Science -- Experiments; Fungi; Experiments